2019
DOI: 10.1007/s42995-019-00010-5
|View full text |Cite
|
Sign up to set email alerts
|

Receptor, signal transduction and evolution of sweet, umami and bitter taste

Abstract: Like olfaction, the sense of taste allows the detection and discrimination of chemicals in the environment. However, while olfaction is specialized in the detection of volatile chemicals, taste is restricted to the detection of contact-chemicals. Two families of mammalian taste receptors, T1R and T2R, involved in recognition of sweet, umami (the taste of monosodium glutamate) and bitter stimuli have been identified and characterized. Although much progress has been made in studies on the basic mechanisms of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 124 publications
(182 reference statements)
0
7
0
Order By: Relevance
“…22 The extracellular domain structures of the sweet and bitter taste receptors consist of multiple rings and cavities, which play essential roles in ligand recognition. 11 In the current study, 169 candidate umami molecules with bitter and sweet taste receptors were docked to verify the authenticity of forecasting results. The heterodimer T1R2/T1R3, which binds to sweet substances, has a Venus Fly Trap domain that is considered a ligand-binding domain activated by most sweet substances.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…22 The extracellular domain structures of the sweet and bitter taste receptors consist of multiple rings and cavities, which play essential roles in ligand recognition. 11 In the current study, 169 candidate umami molecules with bitter and sweet taste receptors were docked to verify the authenticity of forecasting results. The heterodimer T1R2/T1R3, which binds to sweet substances, has a Venus Fly Trap domain that is considered a ligand-binding domain activated by most sweet substances.…”
Section: Resultsmentioning
confidence: 94%
“…10 Similar to the mechanism of sweet and bitter transduction, umami transduction also involves binding taste-presenting substances to specific taste receptors on the taste cell plasma membrane. 11 The umami, sweet, and bitter taste receptors have a complex relationship. All of these receptors are structurally mediated by G protein-coupled receptors, known as the seven transmembrane receptors, whose common feature is the presence of seven α-helical trans-membrane domains with three extracellular and three intracellular loops.…”
Section: Introductionmentioning
confidence: 99%
“…Sweetness detection in the oral cavity of the taster occurs in type II cells and is mediated by a heterodimer receptor called T1R2/T1R3 that is coupled to the G protein superfamily [ 44 , 62 , 63 , 65 , 66 ]. The transduction mechanism of the umami taste modality is very similar to the sweet-taste mechanism [ 67 , 68 , 69 ]. The prominent taste receptor is also a heterodimer belonging to the G-protein coupled receptors but formed by T1R1/T1R3 proteins [ 44 , 64 , 68 , 70 , 71 ].…”
Section: Chestnut Sensory Pleasantnessmentioning
confidence: 99%
“…The transduction mechanism of the umami taste modality is very similar to the sweet-taste mechanism [ 67 , 68 , 69 ]. The prominent taste receptor is also a heterodimer belonging to the G-protein coupled receptors but formed by T1R1/T1R3 proteins [ 44 , 64 , 68 , 70 , 71 ]. Several studies have revealed that medium/high concentrations of monosodium glutamate increase the perception of salty taste, modulate that of sweet taste, and suppress the perception of sour and bitter tastes [ 71 , 72 ].…”
Section: Chestnut Sensory Pleasantnessmentioning
confidence: 99%
See 1 more Smart Citation